Exploring the potential of the philanthropic Islamic financial instruments in providing healthcare services for underprivileged - Jamaluddin, Khairul Fikry; Benaicha, Mohamad; Hassan, Rusni (2020)
Philanthropic financial instruments utilize donated funds or assets in order to deliver social services for society. NGOs may not be able to operate the social services efficiently in the absence of such funds. Lately, there are plenty of organizations that have taken initiatives to render social services for targeted populations in order to curb social problems such as poverty, hunger, crimes, etc., through the use of some forms of philanthropic instruments including Islamic social finance, ethical finance and others. Today, however, the philanthropic financial instruments such as socially responsible investment (SRI), social impact bonds (SIB) and even Waqf are issued by financial institutions rather than socially driven institutions. As such, they have been treated as commercial financial instruments rather than socially driven mechanisms. This paper aims to elucidate the potential of the chosen modern financial philanthropic instruments that deal with the healthcare sector. Furthermore, the strengths and weaknesses of the chosen instruments will be assessed to explore their potential in serving the healthcare services sector particularly for underprivileged. The healthcare sector is chosen as the focus of this study due to its relevance to the present challenge of the Covid-19 pandemic. This is an exploratory study which adopts the qualitative method whereby library research will be conducted using the primary and secondary data. The findings elaborate three important models of philanthropic instruments, namely SIB, DIB and takaful-waqf models. It was also found that these philanthropic instruments have varied strengths and weaknesses that require rectification in the future.